Multiplicity of Asymptomatic Plasmodium falciparum Infections and Risk of Clinical Malaria: A Systematic Review and Pooled Analysis of Individual Participant Data. (4th October 2019) - Eldh, Martina; Hammar, Ulf; Arnot, David; Beck, Hans-Peter; Garcia, André; Liljander, Anne; Mercereau-Puijalon, Odile; Migot-Nabias, Florence; Mueller, Ivo; Ntoumi, Francine; Ross, Amanda; Smith, Thomas; et al.
Abstract: Background: The malaria parasite Plasmodium falciparum holds an extensive genetic polymorphism. In this pooled analysis, we investigate how the multiplicity in asymptomatic P. falciparum infections—that is, the number of coinfecting clones—affects the subsequent risk of clinical malaria in populations living under different levels of transmission. Methods: A systematic search of the literature was performed to identify studies in which P. falciparum infections were genotyped in asymptomatic individuals who were followed up prospectively regarding the incidence of clinical malaria. Individual participant data were pooled from 15 studies (n = 3736 individuals). Results: Multiclonal asymptomatic infections were associated with a somewhat increased subsequent risk of clinical malaria in the youngest children, followed by an initial declining risk with age irrespective of transmission intensity. At approximately 5 years of age, the risk continued the gradual decline with age in high-transmission settings. However, in older children in moderate-, low-, and seasonal-transmission settings, multiclonal infections were either not significantly associated with the risk of subsequent febrile malaria or were associated with an increased risk. Conclusions: The number of clones in asymptomatic P. falciparum infections is associated with different risks of subsequent clinical malaria depending on age and transmission intensity. Abstract : Asymptomatic Plasmodium falciparum infections are often composed of multiples clones. This pooled analysis of individual data shows that the number of clones predicts different subsequent risk of developing clinical malaria depending on age and transmission intensity.